Incidence injury analysis on rowers in the spanish mediterranean fixed bench championship 2012 - Penichet-Tomás, A.; Jiménez-Olmedo, J. M.; Saiz-Colomina, S.; Jove-Tossi, M. A.; Martinez-Carbonell, J. A.; Silvestre-Garcia, M. (Journal of Human Sport & Exercise, 2012)
The standardized assessment of sports injuries provides important epidemiological information and instructions to prevent them. The aim of this study was to determine if the pattern detrimental impact on fixed seat rowing agreed with the literature review of the Olympic rowing modality. A retrospective questionnaire was administer to 79 male rowers, with an age mean of 27.66 ± 7.15, belonging to the male in the senior category VIII Rowing Spanish Mediterranean Bank Fixed Championship that took place in Torrevieja during the 25th, 26th and 27th of May. The anatomical regions that were damage the most were the ankle (15.4%) and lower back (13.2%). These injuries have occurred with higher incidence in training (55.1%) as the most recidivist injury, the ankle, which has occurred for 73% of the time during this moment. The most common injury is the overuse (44.2%) and the most repeated diagnosis was sprain (23.1%).